Administracja publiczna z perspektywy antropologii kulturowej. Kilka uwag o problemach współczesności - Sługocki, Janusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The article presents directions and possibilities of study the problems of public administration from perspective of cultural anthropology. The analysis of public administration from the perspective of the cultural anthropology distinguishes itself first of all with the regard of the wide cultural context. Particularly so-called applied anthropology refers to the application of anthropological theories and methods to identify and solve social problems which are important for public administration. Public administration is observed in the context of cultural changes and processes of social, economic and legal transformation, like European integration and globalization.
Keywords: globalization; applied anthropology; cultural anthropology; European integration; public administration